Let the two factors be x and y.
Two factors that multiply to -1: [tex]xy = -1[/tex]
Two factors that add to 1: [tex]x + y = 1[/tex]
From the second equation: [tex]x = 1-y[/tex]
Plug x back into the first equation: [tex](1-y)(y) = -1 \\ y-y^2 = -1 \\ y^2-y-1 = 0[/tex]
There are no binomial pairs that result in this quadratic. Thus we must use the quadratic formula.
[tex]y^2-y-1=0[/tex]
[tex] \frac{-b+- \sqrt{b^2-4ac} }{2a} \\ \\ \frac{1 +- \sqrt{1-4(1)(-1)} }{2} \\ \\ \frac{1 +- \sqrt{5} }{2} [/tex]
x = -y = [tex]\frac{1 +- \sqrt{5} }{2} [/tex]
Either x or y could be the positive factor. The other variable would have to be the negative factor.
Just a sidenote: [tex]\frac{1 +- \sqrt{5} }{2} [/tex] is actually called the "Golden Ratio" because the ratio is found so often in beautiful example in nature.